1986
DOI: 10.1136/gut.27.5.491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nitrosamine hypothesis of gastric carcinogenesis in precancerous conditions.

Abstract: SUMMARY A 24 hour gastric aspiration study was carried out on nine Polya gastrectomy, eight pernicious anaemia, and nine matched control subjects. Intragastric pH, bacteria, nitrite, and Nnitroso compounds were assessed half hourly whilst ambulant and hourly when in bed. Both total and nitrate reducing bacterial counts were positively related to pH (x2=279-3; p<0.001), as was nitrite concentration (F=19.1; p<00001). By contrast, total (F=40.6; p<00001) and stable (F=257.4; p<0.0001) N-nitroso compound concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
4
26
3
Order By: Relevance
“…Among reports on gastric juice NOC assays in patients with partial gastrectomy for peptic ulcer [3, 18, 20 -24], the data reported by Schlag et al [3] and Sturniolo et al [25] were criticized because of inadequate analytical methods [26,28]. In the controversy about NOC production in the hypochlorhydric stump, our data confirm previous observations [23,26] relating increased NOC levels with pH elevation in Billroth II patients, a correlation not observed by others [21,24,27]. Our data support the findings of Reed et al [23], as we also found significantly higher mean gastric juice NOC levels in patients with gastric resections compared with normal controls.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among reports on gastric juice NOC assays in patients with partial gastrectomy for peptic ulcer [3, 18, 20 -24], the data reported by Schlag et al [3] and Sturniolo et al [25] were criticized because of inadequate analytical methods [26,28]. In the controversy about NOC production in the hypochlorhydric stump, our data confirm previous observations [23,26] relating increased NOC levels with pH elevation in Billroth II patients, a correlation not observed by others [21,24,27]. Our data support the findings of Reed et al [23], as we also found significantly higher mean gastric juice NOC levels in patients with gastric resections compared with normal controls.…”
Section: Discussionsupporting
confidence: 90%
“…Our data support the findings of Reed et al [23], as we also found significantly higher mean gastric juice NOC levels in patients with gastric resections compared with normal controls. This was not observed by other authors [21,24,27] who claimed that the postulated role of NOCs in the Correa multistage hypothesis of gastric carcinogenesis required further confirmation. In our opinion, the contradictions to the reported data are due to four reasons: (a) different sampling modalities; (b) different analytical methods; (c) different time intervals between sample collection and analysis; (d) a lack of patient homogeneity.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, the nitrosamine hypothesis is unproven, and has recently been criticized, because nitrosation is chemically rather than bacterially me diated, i.e. favoured by low rather than high pH [28,29]. This cannot be discussed further in the framework of this review.…”
Section: Hormones and Gastric Adenocarcinomamentioning
confidence: 83%
“…This "N-nitroso compounds" theory has provided a potential explanation for some geographic regions at a very high risk for gastric cancer [29] . But whether this theory can work as well to interpret the high incidence of gastric cancer in the postgastrectomy patients is still a matter of dispute [30][31][32][33][34] . Although we did not measure the concentrations of N-nitroso compounds directly, the initiating assay can effectively detect the mutagenicity of the whole human reflux juice that may contain various mutagenic or carcinogenic substances inclusive of the N-nitroso compounds.…”
Section: Discussionmentioning
confidence: 99%